(3GdeSFhdjI GdLfGFjI Yf LQjeI ZSd GdCehGd aj GdJTQjY GdeUQj (B: s (3OQGSI ebGQfI (B/ s - (3YGOd eMeO CMeO LGHQ GdSjhis; (3eCehf eMeO SdGeI (B: s; (3eMehO SdjeGf cHjT (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3Gf GdJWhQGJ GdGbJUGOjI GdeJdGMbI hGdGMOGK GdJGQjNjI GdJi TgOJgG GdeYehQI Ydi GeJOGO GdGdajI GdefUQeI bO GMOKJ GKGQG YejbI (B: (3hJZjQGJ LPQjI ai eSGQGJ MjGI GdHTQ HeNJda efGMjgG (B: (3hCaVJ Gdi HRhZ YUQ GdYGdejI GdPi LYd GdYGde HCSQg bQjI chfjI UZjQI HaVd KhQI GdGJUGdGJ hGdJWhQGJ GdePgdI ai JbfjI GdeYdheGJ (B: (3hgh eG GSJJHY JfGejG gGFdG eWQOG ai MQcI GdGehGd (B: (3hMQjI JfbdgG hJMhjdgG YHQ GdMOhO GdhWfjI ef NdGd fXe eGdjI YGdejI hGSYI GdGfJTGQ SQjYI GdMQcI HGdZI GdJYbjO (B: (3hbO LYdJ gPg GdJWhQGJ GdfXGe GdeGdi GcKQ YQVI Yf Pi bHd deNGWQ GfJTGQ GdGfTWI GdGLQGejIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2007.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B955 - 1023s
Keywords: (3GdbGfhf GdLfGFjs; (3LQjeI ZSd GdCehGds; (3GdeSFhdjI GdLfGFjIs; (3YedjGJ ZSd GdCehGds; (3GdLQjeI GdefXeIs; (3GdGJLGQ ZjQ GdeTQhYs; (3bGfhf GdcSH ZjQ GdeTQhYs; (3bGfhf ecGaMI ZSd GdCehGds; (3GdWHjYI GdbGfhfjI ddLQGFe GdEQgGHjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs